Management of Different Dairy Production Systems in Sindh - Huma Rizwana; Muhammad Khaskheli; Ghous Bakhsh Isani; Gul Muhammad Baloch (Journal of Basic & Applied Sciences, 2017)
The study of management of different dairy production system in Sindh was conducted in randomly selected from three zones consisting of nine districts of Sindh province of Pakistan. The data was collected from central zone consisting of three districts (Hyderabad, Mirpurkhas and Shaheed Benazirabad) in 2005-06, from upper zone (districts i.e. Larkana, Sukkur and Shikarpur) in 2006-07, and from lower Sindh zone(Karachi, Thatta and Badin) in years 2007-08. The educational status indicated that the graduate dairy farmers were significantly (P<0.05) high (21.11%) at urban dairy farming systems compared to peri-urban, rural market oriented, rural subsistence and mixed dairy farming systems. The results shows that urban and peri urban farming mostly was operated by ? 40 years of age group but under, rural market oriented , rural subsistence and mixed dairy farming ?50 years of age group. The average herd size of urban dairy farming system was (52.67 animals per farm) higher as compare to peri-urban, rural market oriented, mixed and rural subsistence dairy farming system in upper zone. In central zone the results showed that the average herd size of peri-urban dairy farming system was significantly (100.00/farm) higher followed by other farming systems. The average herd size under urban dairy farming system in lower zone observed significantly (P<0.05) high (167.00/farm) as compared to other dairy farming systems. The overall average annual inventories at the beginning of the year urban, peri-urban, rural market oriented, rural subsistence and mixed farming were 129049, 82920, 74634, 35300 and 46658 rupees, respectively and averaging 73712 rupees. The total cost were relatively higher Rs.64506 per animal under urban farming, and the lowest total costs of Rs.31884 per animal were noted under mixed farming system. The total income generated by operators of urban dairy farms in nine districts were recorded high followed by peri-urban, rural market oriented, rural subsistence and mixed dairy farming system. It was observed that from the results that the cost: benefit ratio was significantly higher 1:0.47 under mixed farming system, followed by rural market oriented farming with average cost benefit ratio of 1:0.44. However, the cost benefit ratio under peri-urban, urban, rural subsistence dairy farming systems was 1:0.42, 1:0.36 and 1: 0.34 respectively. The results indicated that the capital turnover was higher 5.66 in case of urban farming indicating that the entrepreneur of urban dairy farming system will recoup their capital investment in 5.66 years, while the capital turnover of peri urban, rural subsistence, rural market oriented and mixed dairy farming systems was 4.33, 4.25, 3.82 and 3.72 indicates that they will recoup their capital investment in 4.33, 4.25 and 3.82 years, respectively. However, the entrepreneurs of mixed farming system will recoup their capital investment in 3.72 years, respectively.